2020
DOI: 10.1017/s0022149x20000036
|View full text |Cite
|
Sign up to set email alerts
|

Insights from new cestodes of the crocodile shark,Pseudocarcharias kamoharai(Lamniformes: Pseudocarchariidae), prompt expansion ofScyphyophyllidumand formal synonymization of seven phyllobothriidean genera – at last!

Abstract: Three new cestode species are described from the crocodile shark (Pseudocarcharias kamoharai) in Ecuador. All three were examined with light and scanning electron microscopy. The unique combination of morphological features in one of the new species prompted formal investigation of the non-monophyly of Paraorygmatobothrium relative to the morphologically similar genera Doliobothrium, Guidus, Marsupiobothrium, Nandocestus, Orectolobicestus, Ruhnkecestus and Scyphophyllidium. Sequence data generated for part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…The LSU was selected as elective target for the analysis, as it is the most used molecular marker for identifying Cestoda [ 3 , 26 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], sometimes in combination with the small subunit (SSU) rRNA gene [ 39 , 40 , 41 ]. Although Olson et al [ 40 ] indicated that the D2 region of the LSU gene exhibited sufficient variability to be useful for species-level identification, a low interspecies variability has been reported by other authors [ 35 ], and other genes, such as COI and ITS, were proposed as alternative markers for distinguishing closely related species of Phyllobothriidae [ 35 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The LSU was selected as elective target for the analysis, as it is the most used molecular marker for identifying Cestoda [ 3 , 26 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], sometimes in combination with the small subunit (SSU) rRNA gene [ 39 , 40 , 41 ]. Although Olson et al [ 40 ] indicated that the D2 region of the LSU gene exhibited sufficient variability to be useful for species-level identification, a low interspecies variability has been reported by other authors [ 35 ], and other genes, such as COI and ITS, were proposed as alternative markers for distinguishing closely related species of Phyllobothriidae [ 35 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Until recently, only three species were reported in the genus Clistobothrium : C. montaukensis , C. carcharodoni and C. tumidum [ 44 ]. However, Caira et al [ 34 ] have very recently described two new species ( C. amyae and C. gabywalterorum ) and suggested an expansion of the total number to six, including the undescribed species C. cf. montaukensis reported by Brickle et al [ 3 ] and Randhawa and Brickle [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations